Conditioning Perspectives for Primary Immunodeficiency Stem Cell Transplants - Shaw, Peter; Shizuru, Judith; Hoenig, Manfred; Veys, Paul; , IEWP-EBMT (Frontiers in Pediatrics, 2019)
The majority of children undergoing Hematopoietic Stem cell Transplantation (HSCT) require conditioning therapy to make space and prevent rejection of the donor stem cells. The exception is certain children with Severe Combined immune deficiency, who have limited or no ability to reject the donor graft. Transplant conditioning is associated with significant morbidity and mortality from both direct toxic effects of chemotherapy as well as opportunistic infections associated with profound immunosuppression. The ultimate goal of transplant practice is to achieve sufficient engraftment of donor cells to correct the underlying disease with minimal short- and long-term toxicity to the recipient. Traditional combinations, such as busulfan and cyclophosphamide, achieve a high rate of full donor engraftment, but are associated with significant acute transplant-related-mortality and late effects such as infertility. Less “intensive” approaches, such as combinations of treosulfan or melphalan with fludarabine, are less toxic, but may be associated with rejection or low level chimerism requiring the need for re-transplantation. The major benefit of these novel approaches, however, which we hope will be realised in the decades to come, may be the preservation of fertility. Future approaches look to replace chemotherapy with non-toxic antibody conditioning. The lessons learnt in refining conditioning for HSCT are likely to be equally applicable to gene therapy protocols for the same diseases.